Juridical Analysis of the Obligations Batam Free Trade Zone and Free Port Enterprise Agency (BP BATAM) to Problematic Land Allocation Recipients - Jurhan Panangian Siallagan; Fadlan; Erniyanti; Soerya Respationo (International Journal of Sustainability in Research, 2023)
BP Batam has very broad authority to manage Batam Island in order to attract investors to invest their capital in Batam Island. Land problems that occur in the city of Batam must be resolved by BP Batam as the authority holder for management rights in Batam in accordance with Head of BP Batam Regulation No. 26 of 2021 concerning Implementation of Land Management. The study's goal is to find out how BP Batam's duties to people who receive land allocations for problematic land are carried out and what factors affect those duties. This research uses empirical juridical qualitative methods, using one legal action against problematic land as a sample. Findings from the study show that BP Batam's duties and goals have been met in how they handled their responsibilities to people who were given problematic land. The obstacles faced so far are due to the lack of communication between BP Batam and the communities that receive problematic land allocations in the city of Batam. BP Batam's obligations are stated to be limited to planning the allocation and use of land and exploiting or using land for purposes of carrying out its duties. Implementation is proven by monitoring and taking action against problematic land, which is the authority of BP Batam.